The Government of Life : Foucault, Biopolitics, and Neoliberalism - Francesco Paolo Adorno; Vatter, Miguel; Lemm, Vanessa (Book collections on Project MUSE., 2014)
This volume focuses on the relation that Foucault established between the ideas of biopower and biopolitics and the studies of governmentality in his last Courses at the College de France and in his occasional writings of this period. The essays in this volume adopt and contribute to Foucault's analysis of biopolitics as a guiding thread to understand why liberalism and neoliberalism is a 'government of life'.